Design and Implementation of Intercity EMUs TCMS - XIAO Jiabo; YANG Weifeng; LI Ming; CHEN Mingfeng; WU Changyou (机车电传动)
The design idea, system structure, main function and characteristics of TCMS on intercity EMUs; were introduced. The typical application showed that TCMS using the two-level network structure for communication and control, achieved the optimal state of the train control through the mutual cooperation of the network, and provided important guarantee for the development and application of TCMS technology.